Bullying victimization among Lebanese adolescents: The role of child abuse, Internet addiction, social phobia and depression and validation of the Illinois Bully Scale - Diana Malaeb; Emmanuelle Awad; Chadia Haddad; Pascale Salameh; Hala Sacre; Marwan Akel; Michel Soufia; Rabih Hallit; Sahar Obeid; Souheil Hallit (BMC, 2020)
Abstract Background Both bullying victimization and perpetration were associated with depression, social phobia, physical and psychological child abuse and Internet addiction in Lebanon. The prevalence of bullying in Lebanon is alarming, with 50% of school-aged children and adolescents reporting being bullied at some point. The high rate of both bullying victimization can be reflective of the inefficacy of current prevention and intervention policies in targeting associated problematic individual and contextual factors. The objective of the present study was to analyze factors associated with bullying victimization and validate the Illinois Bully Scale among Lebanese adolescents. Methods This is cross-sectional study that took place between January and May 2019. We enrolled 1810 adolescents between 14 and 17 years of age. The Illinois Bully scale was used to measure bullying victimization. In order to ensure the adequacy of the sample with values greater than 0.8 - an indicator that component or factor analysis was useful for these variables - we used Kaiser-Meyer-Olkin (KMO) measurement. Statistical significance considered if the p-value < 0.05. Results The results showed that 841 (46.5%, CI: 44.1% - 48.7%) participants were classified as having been previously bullied. None of the bullying scale items was removed. Items on the bullying scale converged on a two-factor solution with Eigenvalues greater than 1, accounting for a total of 73.63% of the variance (Factor 1: bullying victimization; Factor 2: bullying perpetration; KMO = 0.899, Bartlett's sphericity test p < 0.001; αCronbach = 0.955). Having a separate parents (ORa = 3.08), Mild (ORa-4.71) to moderate (ORa = 3.84) internet addiction test, higher social fear (ORa = 1.50), higher psychological abuse (ORa = 3.59), higher child neglect (ORa = 2.21) and physical (ORa = 4.55) abuse were significantly associated with higher odds of being bullied. However, higher social avoidance (ORa = 0.49), poor (ORa = 0.20), fair (ORa = 0.94) and very good (ORa = 0.04) physical activity as compared to sedentary were significantly associated with lower odds of being bullied. Conclusions Our findings attest that bullying victimization is likely to be associated with certain factors such as child abuse of all forms, Internet addiction, social fear and avoidance. In addition, the Illinois Bully Scale was validated in Lebanon. More attention should be paid to students vulnerable to bullying victimization, such as those with environmental or domestic problems, and adolescents with psychological disorders such as behavioral addictions.